Cross-Fostering Implications for Pig Mortality, Welfare and Performance - Calderón Díaz, Julia A.; García Manzanilla, Edgar; Diana, Alessia; Boyle, Laura A. (Frontiers in Veterinary Science, 2018)
This study aimed to 1) identify cross-fostering (CF) practices employed on a commercial farm; 2) characterise CF pigs according to litter of origin traits and 3) investigate the implications of CF practices on pig mortality, performance and welfare. This was an observational study whereby pigs were managed according to normal farming practice. Pigs (n=1,016) born within 1 week were classified as non-CF (NCF); CF during the first (CFW1) and second or third (CFW2+) weeks of lactation. Pigs were individually weighed and inspected for the presence of tail (TL), ear (EL) and body lesions (BL) at weaning (7.03±1.61kg) and at the end of the first (12.9±3.03 kg) and second (31.9±5.50 kg) weaner and grower (66.3±9.12 kg) stages. Mortality was recorded through to slaughter (c. 115 kg). At slaughter, TL were scored and carcass characteristics, presence of pleurisy, enzootic pneumonia, pericarditis and heart condemnations were recorded. 40.8% of CF pigs were CFW1; ANOVA tests revealed these were born to sows with a higher number of piglets born alive than NCF pigs (14.6±2.61 and 12.8±2.68, respectively). The remaining 59.2% of CF pigs were CFW2+; these were, on average, 0.14 kg lighter at birth than NCF pigs. Therefore, a nested case control design was retrospectively applied whereby pigs with complete records to slaughter, were matched for these variables to investigate associations between CF weeks, welfare and performance traits. Growth performance did not differ between CF week (P > 0.05); however, CFW2+ carcasses were 4.9 kg lighter (P < 0.05) compared with NCF and CFW1 pigs. EL were more likely in CFW1 compared to NCF and CFW2+ (P < 0.05) pigs. To investigate the effect of CF week on the risk of mortality, all 1,016 pigs were used. CF pigs were at higher risk of death (P < 0.05) with similar odds in CFW1 and CFW2+ pigs compared with NCF pigs, although other underlying factors could contribute to this result. Performance and health traits were similar between CF weeks. Early cross-fostering appeared to influence the presence of ear lesions but the mechanism is likely indirect and difficult to explain.